Sevoflurane attenuates brain damage through inhibiting autophagy and apoptosis in cerebral ischemia-reperfusion rats - Shi, Cun-Xian (Mol Med Rep, 2020)
The present study aimed to investigate the effects of sevoflurane post-conditioning in a rat brain cerebral ischemia-reperfusion (I/R) model and examine its possible mechanism. Rats were randomly divided into six groups: Sham control group (Sham), I/R group, sevoflurane group (Se), Toll-like receptor-4 (TLR4) inhibitor group (Tak-242), nuclear factor (NF)-κB inhibitor group (QNZ) and Sevoflurane post-conditioning combined with TLR4-NF-κB signaling pathway inhibitor group (Se + Tak-242). Morris water maze test and tetrazolium chloride staining were used to investigate the I/R injury. The nerve cell apoptosis and autophagy in cortical tissue were detected by TUNEL and transmission electron microscopy, respectively. The expression of TLR4 protein in cortical tissue was observed by immunohistochemical staining. The expression of autophagy and apoptotic associated proteins in cortical tissues and the activity of TLR4-NF-κB signaling pathway were assayed by western blot analysis. Sevoflurane post-conditioning improved the learning and memory dysfunction caused by cerebral I/R injury. The cerebral infarction area, nerve cell apoptosis and formation of autophagic vacuoles were reduced after sevoflurane administration. The expression of light chain 3II/I, Beclin-1, Bad and Cleaved-Caspase-3 proteins were inhibited and the expression of Bcl-2 protein was upregulated after sevoflurane administration. Sevoflurane post-conditioning also inhibited the TLR4 protein and NF-κB phosphorylation, and increased inhibitor of kBα phosphorylation. The treatment effect of Tak-242 and QNZ groups were not significantly different compared with the Se group (P>0.05), and the Se + Tak-242 group had the best results. The present study demonstrated that sevoflurane post-conditioning could protect middle cerebral artery occlusion-induced brain injury rats by inhibiting autophagy and apoptosis, and that its mechanism is related to the TLR4-NF-κB signaling pathway.